(untitled) (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2025)
Scientific publications are a crucial aspect for academics. These publications are prepared using structured, systematic, and logical language. One of the key efforts to enhance student competency in publishing within reputable journals is by providing scientific mentoring. This mentoring activity aims to assist students in improving their competencies and soft skills, particularly in producing publications for internationally reputable journals, with a focus on book reviews. The mentoring process is conducted through various methods, including section sharing, discussions, and the provision of empirical experiences and practical guidance. The implementation of this activity consists of three stages: planning, execution, and monitoring-evaluation. The materials provided cover general guidelines for book review manuscripts, timeline preparation, tips and tricks for selecting books, strategies for identifying appropriate journals, and key considerations for successful publication. Results and Outcomes: Based on the activities conducted, a significant improvement in soft skills was observed after the post-test. The results indicate an increase in participants’ performance, with scores improving from an initial range of 1.5–2.00 to 2.5–2.75. Additionally, seven book reviews have been submitted to various reputable journals, with their statuses currently under review or revision. Most submissions are in journals ranked in the Q2 category. Recommendations and Challenges: Moving forward, it is recommended to increase the number of book reviews conducted by participants and to expand opportunities for publication. Some challenges encountered during the preparation of book reviews include limited writing skills, difficulties in accessing information on OJS (Open Journal Systems), inadequate foreign language proficiency, and a lack of collaboration and discussion with other academics. — Publikasi ilmiah menjadi salah satu aspek penting bagi seorang akademisi. Publikasi ilmiah disusun dengan menggunakan bahasa yang terstruktur, sistematis, dan logis. Hal penting yang dilakukan dalam peningkatan kompetensi mahasiswa dalam publikasi di jurnal bereputasi dengan melakukan pendampingan ilmiah. Kegiatan pendampingan ini bertujuan untuk membantu mahasiswa dapat meningkatkan kompetensi dan softskill dalam peningkatkan publikasi di jurnal bereputasi internasional khususnya pada book review. Pendampingan ini dilakukan dengan berbagai metode antara lain sharing section, diskusi, dan pengalaman empiris dan penyusunan praktis. Pelaksanaan kegiatan dilaksanakan dalam tiga tahapan antara lain perencanaan, pelaksanaan, dan monitoring-evaluasi. Materi yang disampaikan antara lain manuskrip umum book review, penyusunan timeline, tip dan trik dalam pemilihan buku, pencarian jurnal serta poin-poin penting dalam publikasi. Berdasarkan hasil yang telah dilakukan, peningkatan softskill terjadi setelah postest dilaksanakan. Hasil menunjukkan bahwa peningkatan terlihat dari jawaban peserta yang sebelumnya berada pada rentang jawaban 1,5-2,00 meningkat menjadi 2,5-2,75. Terdapat tujuh book review yang telah dikirim ke berbagai jurnal bereputasi dengan status under review dan revisi. Dominan berada pada jurnal dengan status Q2. Saran yang dapat diberikan lebih lanjut adalah peningkatan jumlah book review yang dilakukan oleh peserta dan memperbesar peluang untuk publish. Berbagai permasalahan yang muncul dalam penyusunan book review antara lain kemampuan menulis, kemampuan akses informasi terhadap OJS jurnal, kemampuan bahasa asing, dan rendahnya kolaborasi dan diskusi dengan akademisi lain.